The prognostic impact of COX‐2 expression in breast cancer depends on oral contraceptive history, preoperative NSAID use, and tumor size. Issue 1 (28th September 2016) - Simonsson, Maria; Björner, Sofie; Markkula, Andrea; Nodin, Björn; Jirström, Karin; Rose, Carsten; Borgquist, Signe; Ingvar, Christian; Jernström, Helena
Abstract : The association between tumor cyclooxygenase 2 (COX‐2) expression and breast cancer prognosis has been inconsistent. The purpose of this study was to evaluate the prognostic significance of COX‐2 tumor expression according to adjuvant treatment, and potential effect modifications of non‐steroid anti‐inflammatory drug (NSAID) use, and other tumor and lifestyle factors. A prospective cohort of 1, 116 patients with primary breast cancer in Lund, Sweden, included 2002‐2012 was followed until June 2014 (median 5 years). Tumor‐specific COX‐2 expression was evaluated on tissue microarrays using immunohistochemistry. Associations between COX‐2 intensity (negative, weak‐moderate, high) and patient and tumor characteristics as well as prognosis were analyzed. Tumor‐specific COX‐2 expression was available for 911 patients and was significantly associated with higher age at diagnosis and less aggressive tumor characteristics. Higher COX‐2 expression was associated with lower risk for breast cancer events during the first five years of follow‐up, adj HR 0.60 (95%CI: 0.37‐0.97), per category. The association between COX‐2 expression and prognosis was significantly modified by oral contraceptive (OC) use ( P interaction  = 0.048), preoperative NSAID use ( P interaction  = 0.009), and tumor size ( P interaction  = 0.039). COX‐2 negativity was associated with increased risk for events during the first five years in ever OC users, adj HR 1.94 (1.01‐3.72) and during the 11‐year follow‐up in preoperative NSAID users, adj HR 4.51 (1.18‐11.44) as well as in patients with large tumors, adj HR 2.57 (1.28‐5.15). In conclusion, this study, one of the largest evaluating COX‐2 expression in breast cancer, indicates that the prognostic impact of COX‐2 expression depends on host factors and tumor characteristics. Abstract : What's new? Breast cancer is a heterogeneous disease, and clinicians need to know how to identify which tumors are likely to spread. Expression of COX‐2 has been shown to boost tumor growth, but results have been inconsistent. These authors investigated how COX‐2 expression levels relate to tumor characteristics and prognosis. They showed that the value of COX‐2 as a predictor depends on various tumor characteristics. Higher COX‐2 expression was associated with less aggressive tumor features, they found, as well as a favorable prognosis; a lack of COX‐2 meant more problems, particularly in patients who took oral contraceptives, who took NSAIDs, and those with larger tumors.